ENDOTOXINEMIA AND ATHEROSCLEROSIS - Y. S. Schwarz; M. I. Dushkin (Российский кардиологический журнал)
The background of the hypothesis of the involvement of bacterial lipopolysaccharides in initiation and development of atherosclerosis is presented. Special accent is done on the incidence of endotoxinemia, the time of persistence of bioactive endotoxin in the tissues, association between atherosclerosis and Gram-negative infections, plasma and cellular targets and proatherogenic effects of endotoxin. Suggestion on the possible role of LPS-lipoprotein complexes is proposed and detaily discussed. Literature data on the endotoxin effects upon lipoprotein metabolism and foam cell formation are presented.